The Relics of General Chassé - Trollope, Anthony (Saga Egmont, 2021)
'The Relics of General Chassé' is a humorous short story from Victorian author Anthony Trollope. Set in Antwerp, the story charts the misfortune of the Reverend Augustus Horne, who is holidaying in Belgium where he decides to try on a rather special pair of trousers with disastrous consequences. A comical tale from the much-loved author.-